LITHOSTRATIGRAPHY, PETROGRAPHY AND FACIES ANALYSIS OF THE LATE CENOZOIC SEDIMENTS IN THE FORELAND BASIN OF THE WEST KUNLUN - Zheng H.; Huang X.; Butcher K. (My University, 2006)
The Yecheng profile, lying in the southwest Tarim Basin at the northern foot of the West Kunlun Mountains, comprises 4.5 km of conformable Miocene to Pliocene strata. The lower part of the section, the Wuqia Group, is composed of interbedded red mudstone and pale-coloured fine sandstone with a thickness of 1700 m. The Artux Formation is 800 m thick and composed of mudstone, sandstone with thin gravel and conglomerate beds. The upper part of the section, known as the Xiyu Formation, consists of 2000 m of cobble and boulder conglomerate intercalated with massive siltstone lenses. Compositional study of the sandstones in the Wuqia Group and Artux Formation indicates that they were sourced from low relief areas of the Kunlun region and probably further south from Tibet. The provenance of the conglomerate in the Xiyu Formation is the West Kunlun Mountains. Compositional trends within the conglomerate indicate that Upper Palaeozoic marine, and Mesozoic to Tertiary terrestrial silicic rocks were eroded first, along with the Proterozoic to Lower Palaeozoic Proto-Tethys metasedimentary rocks. Erosion into deeper levels of the Kunlun Mountains provided igneous and high-grade metamorphic sediment, which first appears 640 m above the base of the Xiyu Formation. Lithofacies change from fine-grained mudstone and sandstone to coarse clasts coincides with the onset of aeolian sedimentation, indicating major shift of regional palaeoclimatic regime. Although climatic changes may have played an important role in controlling the sedimentary regime worldwide, our study of the lithostratigraphy and petrography of the Yecheng section suggests that the lithofacies change recorded the progressive unroofing history of the source rocks in the West Kunlun Mountains. © 2006 Elsevier B.V. All rights reserved.
Keywords: FACIES ANALYSIS; LITHOSTRATIGRAPHY; PETROGRAPHY; RISK PERCEPTION; WEST KUNLUN MOUNTAINS; Pliocene; Miocene; Precambrian::Proterozoic; Докембрий::Протерозой; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен